2023
DOI: 10.3390/gels9060450
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Resveratrol in Polymeric Nanogel for Improvement of Its Protective Effects on Cellular and Microsomal Oxidative Stress Models

Abstract: Nanogels are attractive drug delivery systems that provide high loading capacity for drug molecules, improve their stability, and increase cellular uptake. Natural antioxidants, especially polyphenols such as resveratrol, are distinguished by low aqueous solubility, which hinders therapeutic activity. Thus, in the present study, resveratrol was incorporated into nanogel particles, aiming to improve its protective effects in vitro. The nanogel was prepared from natural substances via esterification of citric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…As a conclusion, the loading of resveratrol into the micelles improved its protective effect in the developed method. The results are in agreement with other studies that have reported an improvement of antioxidant and anti-inflammatory activity of resveratrol upon its formulation in nanoparticles [47][48][49][50].…”
Section: Drug-loaded Nanocarrierssupporting
confidence: 93%
“…As a conclusion, the loading of resveratrol into the micelles improved its protective effect in the developed method. The results are in agreement with other studies that have reported an improvement of antioxidant and anti-inflammatory activity of resveratrol upon its formulation in nanoparticles [47][48][49][50].…”
Section: Drug-loaded Nanocarrierssupporting
confidence: 93%
“…This was probably due to the increased aqueous solubility of the drug. Various studies have similarly observed an enhancement of resveratrol's effects after increasing its hydrophilicity [60][61][62].…”
Section: Wound-healing Potential Of Resveratrol In Complexesmentioning
confidence: 91%
“…The results revealed that the standard solution did not affect the migration of the fibroblasts (Figure 3) ison, resveratrol formulated into the complexes demonstrated a trend to enha gration of the cells. This was probably due to the increased aqueous solubility Various studies have similarly observed an enhancement of resveratrol's effe creasing its hydrophilicity [60][61][62].…”
Section: Wound-healing Potential Of Resveratrol In Complexesmentioning
confidence: 95%